MEDIATION OF ISLAMIC THOUGHT THROUGH SOCIAL MEDIA INSTAGRAM ON @RUMAYSHOCOM ACCOUNT - Triyono, Agus; Nurangga, Faruq Arif (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2024)
This research aims to find out how the Instagram account @rumayshocom mediates religion in conveying Islamic da'wah via Instagram social media. This research focuses on da'wah communication related to Islamic law and sharia carried out via the social media Instagram. This research uses a descriptive method and a qualitative approach with data collection techniques through documentation studies on the @rumayshocom Instagram account in the form of screenshots of uploaded preaching content along with caption text accompanying the content and interviews with the @rumayshocom account to help validate the findings. This research uses the concept of mediation to explain the phenomenon of mediated communication. The research results obtained are that the @rumayshocom account mediates religion in conveying Islamic da'wah via the social media Instagram by using media as a language through the application of standard Indonesian and media as an environment through the application of da'wah communication using the bil qalam da'wah method in conveying its messages to the audience.